A study of approach to assessing a functional relationship between solidity ratios for the rope/net part of midwater trawl - L. M. Simkin (Известия ТИНРО, 2020)
In this paper we have analyzed an approach to assessing the relationship between some characteristics of the net panels forming the rope/net cone of a fishing trawl. Using the mathematical relationship of solidity ratios for the rope/net panels, it is possible to analyze existing structures and, furthermore, reduce the time for selecting the prototype trawl. Such mathematical relationship allows faster calculation of new trawl designs which takes into account the production specifics of an enterprise manufacturing the trawl fishing gear. The use of mathematical relationships provides the opportunity to accelerate the process of trawl construction.